The role of human rights non-governmental organisations in the African Union and the New Partnership for Africa's Development - Madlingozi, Tshepo (University of Pretoria, 2006)
Prepared under the supervision of Mr. Tshepo Madlingozi at the Faculty of Law, University of Pretoria, South Africa